Complete Heart Block In Pregnancy : A Case Report - Dhanang Ali Yafi (Majalah Kardiologi Indonesia, 2021)
Background: Complete heart block occurs due to various pathological conditions that cause an infiltration, fibrosis, or lose the connection from a part of the cardiac conduction system. Complete heart  block in pregnancy is often caused by congenital anomalies. Around 30% cases, complete heart block remain asymptomatic and not detected until adulthood and may present in pregnancy state and puerperium. When the reversible cause of the AV Block cannot be found, the permanent pacemaker or temporary pacemaker may be indicated when the patients show the symptoms.